2020
DOI: 10.2139/ssrn.3582527
|View full text |Cite
|
Sign up to set email alerts
|

Autocratization by Decree: States of Emergency and Democratic Decline

Abstract: States of emergency grant chief executives the power to bypass democratic constraints in order to combat existential threats. As such they are ideal tools to erode democratic institutions while maintaining the illusion of constitutional legitimacy. Therefore, states of emergency should be associated with a heightened risk of autocratization-a decline in a regime's democratic attributes. Despite this theoretical link and the contemporary relevance of both autocratization and states of emergency, no prior study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…However, the literature remains equivocal about when and where crises -such as the fulminating Covid-19 pandemic -will accelerate autocratization. Exceptions are Lührmann and Rooney (2020) who illustrate that democracies are more likely to decline under a state of emergency or Windsor et al (2015) who analyze how autocratic leaders rhetorically (over)react to suddenly appearing natural disaster crises.…”
Section: Autocratization During Crises and Covid-19 Government Responsesmentioning
confidence: 99%
“…However, the literature remains equivocal about when and where crises -such as the fulminating Covid-19 pandemic -will accelerate autocratization. Exceptions are Lührmann and Rooney (2020) who illustrate that democracies are more likely to decline under a state of emergency or Windsor et al (2015) who analyze how autocratic leaders rhetorically (over)react to suddenly appearing natural disaster crises.…”
Section: Autocratization During Crises and Covid-19 Government Responsesmentioning
confidence: 99%
“…The Authorization Act, in particular, triggered highly visible international repercussions. 2 Albeit subsequently abolished by Parliament (on 16 June 2020), the coronavirus-related special powers (Lu¨hrmann and Rooney, 2020) are expected to have 'long-lasting consequences . .…”
Section: Immediate Crisis Management Responsesmentioning
confidence: 99%
“…Locke, unfortunately, remains completely silent on procedure, i.e., rules according to which a normal state can be transferred into an exceptional one, and then returned back to a normal state. With hindsight, Rousseau’s assertions also appear optimistic and naïve because it has been shown that emergency provisions have not only been misused frequently (Bjørnskov and Voigt 2021 ) but have served as a welcome instrument of would-be autocrats to put their countries on a path away from the rule of law and democracy (Lührmann and Rooney 2020 ). 16…”
Section: Justifying Emergency Legislation: a Brief Sketch Of The Contractarian Literaturementioning
confidence: 99%